The 'third mission' of universities and the region: comparing the UK, Sweden and Austria - Michaela Trippl; Helen Lawton Smith; Tanja Sinozic (European Regional Science Association (ERSA), 2012)
There is a broad and growing literature on the changing role of universities in regional development. What is still missing, however, is a precise understanding of the "third function" of universities in regions. The aim of this paper is to contribute to a nuanced view of the role of universities in regional development. Based on a literature review and a comparison of different conceptual approaches we intend to enrich our knowledge about the multifaceted activities performed by universities at the regional level. Four conceptualisations of the "third function" of universities and regions are considered. In the first, the university "third function" is conceptualised as part of the changing nature of knowledge production and innovation. In this conceptualisation, universities are seen as producers of new types of "Mode 2" knowledge which is trans-disciplinary and generated with a variety of stakeholders in a context of application. In the second, the university is conceptualised as having a changing role in regional economic development. In this view, universities are seen as central in the emergence, growth, and anchoring of local industry and in local knowledge transfer. In the third set of approaches, the university is viewed as having a social and environmental role, as societal beneficiary providing direct services for the region via, for example, training relevant to immediate communities and considering local environmental sustainability. In the fourth, the "third function" is conceptualised as an emergent evolutionary process of interactions arising from differing conditions, actors, operations and outcomes over time. In this view, the "third function" is conceptualised as an outcome of dynamically evolving "Triple Helix" interactions, where overlapping interests, organisations, and networks between academia, government and industry create conditions for new networks and dynamics with changing degrees of determinism over time. Drawing on an analysis of the theoretical and empirical literature, we will highlight that the four approaches outlined above differ strongly with respect to (i) the conceptual explanations they provide for increasing levels of universities' engagement in regional development; (ii) the specific mechanisms and activities by which universities are seen to contribute to regional growth and innovation; (iii) the identification of potential beneficiaries of such activities; and (iv) the main driving forces and barriers to "third function" activities and related policy implications. Taken together, these approaches allow for a view of universities in regions which captures a broad range of old and new functions, interactions, cumulative processes, actors, unpredictability and contextual specificities in line with an evolutionary view.
Keywords: 330